2018
DOI: 10.1002/mnfr.201800359
|View full text |Cite|
|
Sign up to set email alerts
|

Lactobacillus plantarum C29‐Fermented Soybean (DW2009) Alleviates Memory Impairment in 5XFAD Transgenic Mice by Regulating Microglia Activation and Gut Microbiota Composition

Abstract: FDS and C29 alleviates the decrease in cognitive function and inhibited amyloid-β expression in Tg mice by regulating microglia activation and gut microbiota composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 29 publications
3
74
0
Order By: Relevance
“…However, OK67 or PK16 treatment suppressed the gut microbiota LPS production and Proteobacteria population and reduced blood LPS levels. We also found that HFD induced TNF‐α expression and NF‐κB activation and the infiltration of CD11b + /CD11c + cells, which are immune cells including macrophages and dendritic cells, in the colon of mice. However, oral administration of OK67 or PK16 alleviated colitis in HFD‐induced obese mice: they inhibited HFD‐induced NF‐κB activation, TNF‐α expression, and colon shortening and increased IL‐10 expression.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, OK67 or PK16 treatment suppressed the gut microbiota LPS production and Proteobacteria population and reduced blood LPS levels. We also found that HFD induced TNF‐α expression and NF‐κB activation and the infiltration of CD11b + /CD11c + cells, which are immune cells including macrophages and dendritic cells, in the colon of mice. However, oral administration of OK67 or PK16 alleviated colitis in HFD‐induced obese mice: they inhibited HFD‐induced NF‐κB activation, TNF‐α expression, and colon shortening and increased IL‐10 expression.…”
Section: Discussionmentioning
confidence: 51%
“…Immunostaining analysis of brain and colon slices was performed according to the method of Lee et al . Briefly, the colons were cryosectioned through the coronal plane at a thickness of 30 µm, stored at 4 °C in the storing solution (30% glycerol, 30% ethylene glycol in PBS), permeabilized in 0.5% Triton X‐100, and blocked in 10% bovine serum with Tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…An imbalance in the GM can also directly cause neuroinflammation through the "brain-gut axis" (Daulatzai, 2014). Moreover, alteration of the GM by probiotics inhibits the activation of NF-κB and neuroinflammation and significantly improves cognitive activity (Lee, Hwang, & Kim, 2018). Given that gastrointestinal bacteria secrete inflammatory substances in the hippocampus and neocortex of AD patients (Y.…”
Section: Discussionmentioning
confidence: 99%
“…A spontaneous (actual) alternation was defined as entries into all three arms on consecutive choices and was calculated as the ratio (%) of actual to possible alternations. A novel object recognition (NOR) task was performed in the apparatus consisting of a darkopen field box (45 × 45 × 50 cm) according to the method of Lee et al (47). For the first trial, a mouse was placed in the box containing two identical objects and the frequency of touching each object was recorded for 10 min.…”
Section: Cognitive and Depressive Behavioral Tasksmentioning
confidence: 99%
“…Genomic DNA was extracted from the fresh stools of five mice (not trans-cardiacally perfused with 4% paraformaldehyde for brain and colon tissue sections) using a commercial DNA isolation kit (QIAamp DNA stool mini kit), as previously reported (11,47). Briefly, genomic DNA was extracted from the fresh stools of mice using a commercial DNA isolation kit (QIAamp DNA stool mini kit).…”
Section: Microbiota Sequencingmentioning
confidence: 99%